2020
DOI: 10.3390/ani10112177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Crude Protein on Animal Performance, Blood Biochemistry Profile, Ruminal Fermentation Parameters and Carcass and Meat Quality of Heavy Fattening Assaf Lambs

Abstract: Thirty Assaf male lambs (30 ± 1.9 kg of body weight) were allocated to three groups fed diets differing in their crude protein (CP) contents (low protein (LP), 134 g CP/kg dry matter (DM); medium protein (MP), 157 g CP/kg DM; and high protein (HP), 173 g CP/kg DM) to test the effect of dietary protein content on animal performance, rumen function, animal health, and carcass and meat quality. Feed intake was recorded daily, and animals were weighed every second week. Lambs were blood-sampled to determine their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
13
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 59 publications
9
13
3
1
Order By: Relevance
“…Or may be this result is due to the highest bioavailability of nutrient by balanced energy and protein levels on the treatments (13). This finding is in accordance with those reported in sheep (10,29), as well as in goat (2, 22, 13, 27).…”
Section: Growth Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…Or may be this result is due to the highest bioavailability of nutrient by balanced energy and protein levels on the treatments (13). This finding is in accordance with those reported in sheep (10,29), as well as in goat (2, 22, 13, 27).…”
Section: Growth Performancesupporting
confidence: 93%
“…However, blood urea increased by increasing protein level but the increase was not significant. Similar results have been reported by other researchers (12,15,21,29,34,35).…”
Section: Blood Parameterssupporting
confidence: 93%
“…[ 26 ] in thin-tailed sheep. The previous studies reported that the dressing percentages of different lamb breeds varied from 39% to 51% [ 21 , 25 , 26 , 29 , 30 ]. Valizadeh et al .…”
Section: Discussionmentioning
confidence: 99%
“…The carcass weights obtained in this study were similar to those reported by Setyaningrum et al [26], where Indonesian thin-tailed sheep weighing 17.5-18.8 kg produced 7.7-8.5 kg carcasses. Other studies reported that lamb carcass weights varied from 15.3 kg to 26.1 kg when originating from a slaughter weight of 34.3 kg-54.1 kg [21,[27][28][29][30]. Forwood et al [30] reported that heavier live weights produced higher carcass weights and dressing percentages.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation